Acetylcholinesterase inhibition protects against trastuzumab-induced cardiotoxicity through reducing multiple programmed cell death pathways - Thawatchai Khuanjing; Chayodom Maneechote; Benjamin Ongnok; Nanthip Prathumsap; Apiwan Arinno; Titikorn Chunchai; Busarin Arunsak; Siriporn C. Chattipakorn; Nipon Chattipakorn (BMC, 2023)
Abstract Background Trastuzumab (Trz)-induced cardiotoxicity (TIC) is one of the most common adverse effects of targeted anticancer agents. Although oxidative stress, inflammation, mitochondrial dysfunction, apoptosis, and ferroptosis have been identified as potential mechanisms underlying TIC, the roles of pyroptosis and necroptosis under TIC have never been investigated. It has been shown that inhibition of acetylcholinesterase function by using donepezil exerts protective effects in various heart diseases. However, it remains unknown whether donepezil exerts anti-cardiotoxic effects in rats with TIC. We hypothesized that donepezil reduces mitochondrial dysfunction, inflammation, oxidative stress, and cardiomyocyte death, leading to improved left ventricular (LV) function in rats with TIC. Methods Male Wistar rats were randomly assigned to be Control or Trz groups (Trz 4 mg/kg/day, 7 days, I.P.). Rats in Trz groups were assigned to be co-treated with either drinking water (Trz group) or donepezil 5 mg/kg/day (Trz + DPZ group) via oral gavage for 7 days. Cardiac function, heart rate variability (HRV), and biochemical parameters were evaluated. Results Trz-treated rats had impaired LV function, HRV, mitochondrial function, and increased inflammation and oxidative stress, leading to apoptosis, ferroptosis, and pyroptosis. Donepezil co-treatment effectively decreased those adverse effects of TIC, resulting in improved LV function. An in vitro study revealed that the cytoprotective effects of donepezil were abolished by a muscarinic acetylcholine receptor (mAChR) antagonist. Conclusions Donepezil exerted cardioprotection against TIC via attenuating mitochondrial dysfunction, oxidative stress, inflammation, and cardiomyocyte death, leading to improved LV function through mAChR activation. This suggests that donepezil could be a novel intervention strategy in TIC.